2018
DOI: 10.5937/psistra1801023r
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia measured with the TAS-20 questionnaire: Determining the validity of the factor structure and its relation to life satisfaction and the Big Five personality traits

Abstract: Aleksitimija predstavlja nemogućnost individue da prepozna što sopstvena, što tuđa osećanja i da predoči okolini svoja emotivna stanja. Na kognitivnom nivou uočava se umanjena sposobnost maštanja, praktičan, odnosno konkretan stil mišljenja, dok se na afektivnom nivou aleksitimija manifestuje umanjenom sposobnošću osvešćivanja emocija. Najkorišćeniji instrument za merenje aleksitimije jeste TAS-20 upitnik koji se sastoji od tri supskale: faktor 1-identifikacija osećanja, faktor 2-poteškoće pri opisivanju oseća… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This is in opposition to general findings regarding alexithymia (Timoney & Holder, 2013). Earlier studies examining the Serbian population indicated gender differences in F1, but not in F3 (Rokvic & Jovanovic, 2018). This must be regarded as a peculiarity of the surveyed population.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is in opposition to general findings regarding alexithymia (Timoney & Holder, 2013). Earlier studies examining the Serbian population indicated gender differences in F1, but not in F3 (Rokvic & Jovanovic, 2018). This must be regarded as a peculiarity of the surveyed population.…”
Section: Discussionmentioning
confidence: 68%
“…It consists of three subscales: factor 1 -difficulty identifying feelings (F1), factor 2 -difficulty describing feelings (F2), and factor 3 -externally oriented thinking (F3). The questionnaire was translated into Serbian (Trajanovic, Djuric, Latas, Milovanovic, Jovanovic, & Djuric, 2013), and further validated on a large CIVITAS sample (Rokvic & Jovanovic, 2018). The overall internal consistency of the TAS-20 in our study was on the lower end of acceptable margins (α=.78) and for the subscales, respectively (α=.79, α=.75, α=52), with expectedly low values for the third factor (Rokvic & Jovanovic, 2018).…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…The Toronto Alexithymia Scale [TAS-20] is one of the most commonly used instruments to measure levels of alexithymia. The scale was translated into Serbian [27] but after further validation of its factor structure, item 20 was removed in order to retain its original factor structure [24]. This instrument consists of 3 subscales; factor 1 -difficulty identifying feelings, factor 2 -difficulty describing feelings, and factor 3 -externally-oriented thinking.…”
Section: Methodsmentioning
confidence: 99%
“…Personality traits also have a significant impact on the phenomenon in non-clinical and clinical populations, and are responsible for mediating outcomes in many illnesses designated as psychosomatic, especially Neuroticism, know also as emotional stability [21,22]. Apart from the traditional Big Five personality traits, it has also been shown that alexithymiainability to identify, perceive and value emotions -has a significant effect on the overall health of the population and treatment outcomes [22][23][24]. In light of this, we have decided to include this construct in our study of somatization.…”
Section: Introductionmentioning
confidence: 99%